(untitled) (World Bulletin of Public Health, 2024)
This article critically examines existing literature on chronic allergic rhinitis, offering a comprehensive overview of its fundamental concepts, incidence rates, and pathogenic mechanisms. Through the analysis of available data, it becomes evident that chronic allergic rhinitis is a global health concern, significantly impacting the lives of affected individuals. The pathogenesis of chronic allergic rhinitis is intricately described, involving the interaction of allergens with immunoglobulin E, and the activation of eosinophils, lymphocytes, and interleukins, ultimately leading to the development of allergic inflammation. Despite advancements, both clinical and morphological definitions of chronic allergic rhinitis remain elusive, underscoring the complexity of this condition. The insights derived from this review contribute to a deeper understanding of the widespread prevalence of chronic allergic rhinitis and its profound impact on patient well-being. The delineation of pathogenic processes offers a foundation for further research aimed at refining clinical and morphological definitions, ultimately fostering improved diagnostic and therapeutic strategies for this prevalent and impactful health condition.